A cultura de segurança do paciente em unidades cirúrgicas de um hospital de ensino da rede pública de saúde - Diene Ines Carvalho Moretao (2019)
Offer an assistance with quality and safety in healthcare area is a complex activity that demands several actions. The promotion of a culture that recognizes the possibility of mistakes happening and the learning derivative from it for prevention becomes one of the requirements to achieve success in a treatment without injuries. The objective of this study was to analyse the patient safety culture in the view of the healthcare team that attend surgical patients in a public school hospital in Belo Horizonte. This a mixed study of descriptive-explanatory outline, using triangulation of quantitative methods with the use of Hospital Survey Safety Culture (HSOPSC) questionnaire, fulfilled with 246 professionals of the healthcare team, and qualitative through 21 interviews with a semi-structured script with the nursing team. The average score attributed to patient safety in the studied surgical units was 3,71 in a 1 to 5 scale. The study didnt show evidence of any area of safety culture considered as strong. The culture areas pointed as spheres of higher potential in the safety aspect were teamwork inside the units, expectations about supervisor/manager, organizational learning and continuous improvement and communication opening. The area considered as more fragile was non-punitive response to errors. It was observed a culture with communication problems, distance between managers and staffs, difficulties related to coordination of teamwork between units and lack of effective continued education. The strategy of using mixed methods presented itself very efficient to clarify aspects of safety culture of surgical patients. The integrated analysis of the mixed methods results enabled the elaboration of inferences revealing the presence of a punitive approach which justifies the no error reporting. To improve the culture, it is necessary to perform trainings, better personal sizing, advances in communications and draw managers and team closer.